Evaluating the Relationship Between Anogenital Distance, Reproductive Tract Score, and Fertility to Timed-artificial Insemination in Commercial Bos taurus Beef Heifers - Allen G. Schwartz (Kansas Agricultural Experiment Station Research Reports, 2026)
Objective: This study was to evaluate the relationship between anogenital distance (AGD) and reproductive tract score (RTS) to fertility in commercial beef heifers enrolled in a timed-artificial insemination (TAI) protocol. Study Description: Replacement heifers (n = 888) from eight locations in Kansas and Tennessee were enrolled in TAI synchronization protocols. Heifers were assigned an RTS and measured for their AGD. Heifers were tested by transrectal ultrasound to determine pregnancy to the TAI, and an analysis of pregnancy based on RTS and AGD was done. The Bottom Line: The RTS was a better predictor of pregnancy in virgin beef heifers than AGD. However, when both assessments were combined, there was greater prediction power for pregnancy to TAI.
Keywords: anogenital distance; fertility; reproductive tract score